Some bird records from Obi, Maluku - M D Linsley (Indonesian Ornithologists’ Union, 1995)
From 11 to 23 December 1989 a survey was carried out in agricultural and forested areas of northwest Obi. A total of 65 species was recorded, including Obi's only endemic the Carunculated Fruit-dove Ptilinopus granulifrons, in addition to 10 of the island's 19 endemic subspecies and 7 of the island's 15 Moluccan endemics. Nine species, at least four of which may represent resident populations, were recorded for the first time on Obi. Evidence is provided that the Cacatua alba may not occur on this island (contra White & Bruce 1986). Details of observations of species of particular interest are also provided together with an appendix listing other species recorded.